1981
DOI: 10.1007/bf01068078
|View full text |Cite
|
Sign up to set email alerts
|

Predicting individual phenytoin dosage

Abstract: Most previously suggested methods for predicting phenytoin dosage from steady-state drug levels (Cpss) measured in the clinical setting fail to fully exploit all relevant (population) information. A bayesian prediction method, applicable to any drug, is available. It appropriately combines all types of information. In this paper, we compare the Bayesian method as applied to phenytoin to two other prediction methods (and a baseline, nonfeedback one). Actual doses are compared to predictions in 49 patients. Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 18 publications
3
36
0
Order By: Relevance
“…The pharmacokinetic parameters calculated in group 1 from both the linear and non-linear analysis were very similar to population parameters of patients reported in other studies [24][25][26][27].…”
Section: Discussionsupporting
confidence: 52%
“…The pharmacokinetic parameters calculated in group 1 from both the linear and non-linear analysis were very similar to population parameters of patients reported in other studies [24][25][26][27].…”
Section: Discussionsupporting
confidence: 52%
“…This does not apply, however, to phenytoin, and this drug is dealt with exactly as described by Vozeh et al (1981) (9). This is carried out using a SIMPLEX routine (Nelder & Mead, 1965) and the estimated errors in the parameter values are obiained.…”
Section: (C) Population Estimatesmentioning
confidence: 99%
“…These drug dosing methods include nomograms [1], graphic methods using linear transformations of the Michaelis-Menten equation [2], techniques using population clearance values [3] and Bayesian methods [4]. Today, the Bayesian approach is considered to be the best one according to the precision and the reduced number of deviation errors.…”
Section: Introductionmentioning
confidence: 99%
“…Various previous studies showed that one of the main parameters affecting the predictive performances of such Bayesian method was the number of feedback concentrations from each patient used for predictions [4,15,16]. Therefore, the PKS program was used to predict following phenytoin serum concentration from 1 (data set b) or 2 (data set c) feedback concentrations.…”
mentioning
confidence: 99%